Growth response, heavy metal content, and health risk assessment of Brassica juncea L. and Amaranthus tricolor L. cultivated in urbanized and rural areas - Ramli, Syamira (2019)
Urbanization will lead to changes in socioeconomic structures in Malaysia. It may also lead to changes in the quality of agricultural products due to modified ecosystem. The purpose of this study is to observe and to evaluate the plant growth responses and Health Risk Assessment (HRA) on two selected leafy vegetables. Brassica juncea L. (Brassica sp.) and Amaranthus tricolor L. (Amaranthus sp.) that were grown under urban ecosystem at Seksyen 24, Shah Alam and the rural (traditional) Field of UPM were compared in terms of their growth performance. Growth parameters such as leaf area ratio (LAR), leaf weight ratio (LWR), and specific leaf area (SLA) were determined from the dry weight of plants’ parts that had been oven-dried until constant weight was achieved. Chlorophyll contents were determined using extraction method of fresh leaf in 80% acetone, while photosynthetic parameters (photosynthesis, transpiration rate, and stomatal conductance) were determined using Portable Photosynthesis System (LI- 6400XT). Heavy metals such as copper (Cu2+), iron (Fe2+), and zinc (Zn2+) were determined using a dry-ashing method. Health Risk Assessment (HRA) parameters, Estimated Daily Intake (EDI) and Target Hazard Quotient (THQ) were done according to the formula. The results showed that total dry weight of Brassica sp. was greater when grown in rural area, and greater for Amaranthus sp. when grown in urban area. The LAR values of both species were found to be higher in the samples grown in urban area compared to rural area. The LWR values of Brassica sp. were higher in the samples grown in rural area and LWR of Amaranthus sp. were higher when grown in urban area. The values of SLA were higher in both species grown in urban area compared to rural area. Meanwhile, the chloropyhll content in Brassica sp. were higher in the samples grown in rural area. However, the chlorophyll contents in Amaranthus sp. were higher in the samples grown in urban compared to rural area. All photosynthetic parameters of both species were higher in the samples grown at rural area compared to urban area. Meanwhile, the heavy metals were found to be higher in the samples grown in urban area compared to rural area, except for Zn. HRA assessment showed that no health risk to human when consuming both vegetables grown from both sites since THQ values were less than 1. Urbanization has significant changes on some of the physiological reactions and contamination that occurs in urbanized area may contribute in exposure to health risk.